Divergent population trajectories despite similar response to temperature in a widespread aerial insectivore - Conor C. Taff; J. Ryan Shipley; Daniel R. Ardia; David Aborn; Lauren Albert; Marc Bélisle; Amos Belmaker; Lisha L. Berzins; Tricia Blake; Frances Bonier; Hannah C. Brewer; Michael W. Butler; et al. (Proceedings of the National Academy of Sciences, 2026)
Climate change is shifting when animals breed [C. Parmesan, G. Yohe, Nature 421 , 37–42 (2003) and S. J. Thackeray et al. , Nature 535 , 241–245 (2016)], but it is not clear why some populations keep pace with warming while others fall behind [L. D. Bailey et al. , Nat. Commun. 13 , 2112 (2022) and J. M. Samplonius et al. , Glob. Change Biol. 24 , 3780–3790 (2018)]. Differences could arise from variation in sensitivity to temperature [L. D. Bailey et al. , Nat. Commun. 13 , 2112 (2022)] or constraints on the ability to respond to temperature. Without knowing whether populations differ in sensitivity—or in their ability to act on that sensitivity—we cannot identify which are most at risk. Using 1,555 population-years from 123 populations of tree swallows ( Tachycineta bicolor ), we show that populations have similar sensitivity to local temperature, advancing breeding by about one day per degree of warming. However, northern populations face tighter time constraints and greater exposure to recent warming. Northern populations have advanced laying dates the most, but still experience stronger selection for earlier breeding, especially in warm years; they have also declined most in breeding abundance. These findings suggest that vulnerability to climate change can arise not just from different sensitivity to warming, but from when and where populations can respond effectively. By disentangling sensitivity from timing constraints, our results are consistent with a general mechanism by which even uniformly responsive species can show uneven impacts of climate change across their ranges.